Rape Myths and Domestic Abuse Myths as Hermeneutical Injustices. Issue 2 (23rd February 2016) - Jenkins, Katharine
Abstract: This article argues that rape myths and domestic abuse myths constitute hermeneutical injustices. Drawing on empirical research, I show that the prevalence of these myths makes victims of rape and of domestic abuse less likely to apply those terms to their experiences. Using Sally Haslanger's distinction between manifest and operative concepts, I argue that in these cases, myths mean that victims hold a problematic operative concept, or working understanding, which prevents them from identifying their experience as one of rape or of domestic abuse. Since victims in this situation lack the conceptual resources needed to render their experience sufficiently intelligible, they are suffering a form of hermeneutical injustice. Attending to this distinctive case sheds new light not only on the functioning of social myths of this kind but on the nature of hermeneutical injustice itself, since the case of the victim who accepts myths is importantly different from other cases of hermeneutical injustice discussed in the literature to date. In practical terms, this analysis supports calls for juries in rape trials to be warned about rape myths at the start of the trial, and may have implications for calls for statutory Sex and Relationships Education in schools.